2016
DOI: 10.1038/srep29180
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the morphological architecture of a shape memory polyurethane by simulation

Abstract: The lack of specific knowledge of the network structure in shape memory polymers (SMPs) has prevented us from gaining an in-depth understanding of their mechanisms and limited the potential for materials innovation. This paper firstly reveals the unit-cell nanoscale morphological architecture of SMPs by simulation. The phase separated architecture of a segmented shape memory polyurethane (SMPU) with a 30 wt% hard segment content (HSC, 4,4’-diphenylmethane diisocyanate (MDI) and 1,4-butanediol (BDO)) showing go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…Among these SMPs, SMPUs have attracted more and more attention during the past decades because of their excellent properties such as high tensile strength, high flexibility, high abrasion resistance, good adhesion ability, and so on [9]. SMPUs have become one of the most rapidly developing members of PU industry, and have been applied in many aspects such as coatings, textiles, adhesives, sealant, films, etc [10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these SMPs, SMPUs have attracted more and more attention during the past decades because of their excellent properties such as high tensile strength, high flexibility, high abrasion resistance, good adhesion ability, and so on [9]. SMPUs have become one of the most rapidly developing members of PU industry, and have been applied in many aspects such as coatings, textiles, adhesives, sealant, films, etc [10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…SMPUs have become one of the most rapidly developing members of PU industry, and have been applied in many aspects such as coatings, textiles, adhesives, sealant, films, etc [10]. However, SMPU still has such limitations as lower stiffness and weaker shape recovery force when compared with shape memory alloys and ceramics [9]. Further, like other polymer materials, SMPU is vulnerable to aging and ultimately fails to meet the performance requirements and subsequently limits its practical application when exposed to heat, oxygen or ultraviolet (UV) light during its service life.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Easley et al [ 8 ] compared the mechanical test and micro crack analysis of the SMP foam prepared by the monomer diethanolamine (DEA) and triethanolamine (TEA), and proved that DEA could effectively improve the toughness of materials and reduce micro-cracks. A thermodynamic incompatibility between the soft and hard segments leads to microphase separation and the aggregation of hard segments, which then forms a two-phase structure in SMPU [ 9 ]. The hard segment usually acts as a stationary phase in order to fix the soft segment.…”
Section: Introductionmentioning
confidence: 99%
“…The shape memory behavior in polymers has also been investigated by means of molecular dynamics (MD) computer simulations [47][48][49][50][51][52][53]. In a recent MD-work [51], different models of polymers were analyzed in a shape memory cycle, highlighting the importance of temperature-dependent chain mobility.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent MD-work [51], different models of polymers were analyzed in a shape memory cycle, highlighting the importance of temperature-dependent chain mobility. Another study [53] employed dissipative particle dynamics (DPD) to investigate phase-separation in the polymer network and individual functions of different segments in a polyurethane-based shape memory polymer. As to additive-induced shape recovery, it has been shown that plasticizing effect of additive molecules on structural relaxation in polymers leads to an enhancement of shape recovery rate [50,54,55].…”
Section: Introductionmentioning
confidence: 99%